Gorbachev’s Perestroika and the National Question - Khachatryan, Artak (History and Culture, 2025)
The Soviet Union was a unique state formation where national policy was marked by contradictions: on one hand, it promoted national identity, while on the other, it aimed at assimilation. Soviet ideology treated the national question as secondary, assuming that socialism would erase ethnic distinctions. However, during the Perestroika period, national tensions escalated, contributing to the destabilization of the state. Local conflicts, such as the Fergana and Osh riots, the Georgian-Abkhaz and Nagorno-Karabakh conflicts, and protest movements in the Baltic states and Crimea, highlighted deep-rooted contradictions. The Soviet Union’s ineffective national policy and Gorbachev’s failure to provide a conceptual solution accelerated the USSR’s collapse, making the national question one of the key factors in its downfall.